The Effect of Tempe Yeast Inoculum Amount on the Quantity and Quality of Cocos nucifera viridis Virgin Coconut Oil (VCO) - Adystia, Yusdike; rahmawati, meidina; Anam, Khairul; Iswari, Retno Sri; Dewi, Pramesti (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2021)
This study aims to determine the effect of tempeh yeast inoculum on the color, odor, and yield in the manufacture of Virgin Coconut Oil (VCO) from Cocos nucifera viridis. This research was conducted in November 2020 in Brebes, Magelang, and Lampung. This research employed the descriptive quantitative method. The population of this experiment was coconut fruit found in Lampung, Brebes, and Magelang. The sample used was green coconut (Cocos nucifera viridis) found in Lampung, Brebes, and Magelang. The working procedure of this research consisted of fermenting the sample and observing the oil produced by Virgin Coconut Oil. This research's data collection techniques were observation, documentation, and products calculation. Based on the observations, the researchers found the highest yield in the experiment of 80 ml cream with an inoculum of 8 grams (30.4%), followed by a volume of 80 ml of cream with a 6-gram inoculum (28.4%). The smallest yield was formed at a volume of 80 ml cream with inoculum 4 grams (14.6%). The VCO obtained in this research had a distinctive aroma of coconut oil and was clear in color. Therefore, the amount of tempeh yeast inoculum affects the color, odor, and yield in the manufacture of Virgin Coconut Oil (VCO) from Cocos nucifera viridis.